Prinsip Pengelolaan Dana Desa Terhadap Pertumbuhan Ekonomi Untuk Meningkatkan Kesejahteraan Masyarakat Ditinjau Dari Perspektif Ekonomi Syariah (Studi Kasus Desa Parean Girang Kec. Kandanghaur Kab. Indramayu) - Amal Fazri Nur Ridwan (Jurnal Ilmiah Ekonomi Islam, 2023)
This research was backgrounded by the number of poor people in Parean Girang Village, Kandanghaur District, Indramayu Regency. As we know that poverty is one of the indicators to measure the level of public welfare. The purpose of this study is to determine the principles of management and villages towards economic growth to improve welfare in terms of the Islamic economic perspective. The research method used is quantitative research. Based on the results of research and discussion, it is known that the value of R2 is 0.569. This value comes from the deferment of the value of the correlation coefficient (R), which is 0.755 x 0.755 = 0.569. It is known that the value of the Coefficient of determination is 0.569 or 57%. This means that the variables Adl (X1), Transparency (X2), Ma'ad (X3) affect the variables Public Welfare (Y) by 57%. then it can be summed up as follows; variable 'adl (X1) has no positive and significant effect on community welfare (Y), transparency variable (X2) has a positive and significant effect on community welfare (Y), ma'ad variable (X3) has a positive and significant effect on community welfare (Y), transparency variable (X2) and ma'ad variable (X3) simultaneously or together have a positive and significant effect on community welfare (Y ). While the rest is influenced by other variables outside this regression equation.